A Relook At Visual Privacy: Definition And Factors Influencing Muslim Visual Privacy (MVP) - Azhani Abd Manaf; Zaiton Abdul Rahim; Noor Hanita Abdul Majid; Spahic Omer (UPM PRESS, 2024)
Volume :27 No :4